Wearable Technologies in Athletic Performance - Tolga Şahin (Selcuk University, 2021)
Nowadays, not only training methods but also wearable player tracking systems provided by the developing technology to the experts play an important role in the development of sportive performance. Tracking of external load as work done in high-level athletes and by monitoring the internal load, these systems that train at the desired exercise intensity usage has increased. In addition, wearable technology products, which control the acute and chronic training load and related with increased injury risk, have started to serve as an important feedback mechanism in recovery from injury. It has been used in motion analysis to determine the activity pattern recently and to collect data within the competition. Wearable technology products use different ways such as "Global Positioning System, Local Positioning System, Micro Electromechanical System, Inertial Measurement System" and it should be taken into account that different sensors collect data at different frequencies and process this data with variable algorithms. With the widespread introduction of different commercial products in the last 10 years, using wearable technology can be said to be indispensable helpers for trainers working to improve performance in sports.